Development and evaluation of kraft pulp-banana fibre-reinforced cement composites as a sustainable alternative to asbestos cement boards in Africa - Taiwo, Anuoluwapo Samuel; Khorami, Morteza; Ayre, David; Rahatekar, Sameer S. (Taylor & Francis, 2026)
Many developing countries, particularly in Africa, still rely on carcinogenic asbestos fibres for producing cement boards used in roofing and cladding. This research focuses on creating a sustainable, affordable, and locally available alternative to asbestos. A specialised laboratory technique, designed to mimic industrial asbestos-cement board production, was used to develop kraft pulp–banana fibre reinforced cement composite boards. Their mechanical, durability, and morphological properties were tested after curing in a humidity chamber. Findings showed that boards made with 10 wt.% kraft pulp and 6 wt.% banana fibres achieved the best performance, with a flexural strength of 14.31 MPa and a deflection of 2.15 mm. Physical and morphological assessments confirmed that lightweight boards with strong fibre-matrix bonding can be achieved using kraft and banana fibres. The results also demonstrate that these hybrid fibre-reinforced cement boards meet relevant standards such as BS EN 12467, indicating that they are a safe and effective potential replacement for asbestos-based products.
Keywords: Natural fibre; waste cardboard; fibre cement board; cement composite; mechanical properties; affordable housing; African countries; 40 Engineering; 33 Built Environment and Design; 3302 Building; 11 Sustainable Cities and Communities